Leucocyte esterase, glucose and C-reactive protein in the diagnosis of prosthetic joint infections: a prospective study. (June 2016) - De Vecchi, E.; Villa, F.; Bortolin, M.; Toscano, M.; Tacchini, L.; Romanò, C.L.; Drago, L.
Abstract: Analysis of joint fluid is of paramount importance for the diagnosis of prosthetic joint infections. Different markers of inflammation and/or infection in joint fluid have been proposed for diagnosis of these infections. In this study we evaluated the performance of leucocyte esterase, C-reactive protein (CRP) and glucose assays in synovial fluids from 129 patients with septic ( n  = 27) or aseptic ( n  = 102) prosthetic joint failure. Samples were collected in serum tubes and centrifuged to limit the presence of corpuscle interfering with the assays. Determinations of leucocyte esterase and glucose were carried out by means of enzymatic colorimetric reactions performed on strips for urine analysis. Tests were considered positive when graded + or ++ whereas traces or absence of colour were considered negative. CRP was measured using an automated turbidimetric method and considered suggestive for infections when >10 mg/L. Leucocyte esterase was positive in 25/27 infected patients and negative in 99/102 not infected patients (sensitivity 92.6%, specificity 97.0%). CRP was higher than the threshold in 22/27 infected patients and in 6/102 not infected patients (sensitivity: 81.5%; specificity: 94.1%) whereas glucose showed the lowest sensitivity (77.8%) and specificity (81.4%), being negative in 21/27 and 19/102 infected and not infected patients, respectively. CRP led to a correct diagnosis in 19 of 22 patients with discordant esterase and glucose results. In conclusion, evaluation of leucocyte esterase, glucose and CRP may represent a useful tool for rapid diagnosis of prosthetic joint infections.